ANALISIS PESAN AMANAT DALAM FILM ANIMASI JUMBO (2025): STUDI TENTANG NILAI-NILAI MORAL DAN ETIKA - Wina Wulandari (HIBRUL ULAMA, 2025)
The animated film Jumbo (2025) conveys strong moral messages on social issues such as bullying, self-esteem, and the importance of social and familial support. This study aims to analyze the moral messages in the film using Bandura’s Social Learning Theory, focusing on the four key concepts: observation, imitation, reinforcement, and cognitive evaluation. A descriptive qualitative approach was used to explore and describe the moral meanings taught through the character Don, who faces bullying and other social challenges. The research findings show that the film effectively portrays how Don learns values such as anti-bullying, integrity, empathy, moral courage, and cooperation through social interactions and observing the behaviors of those around him. In conclusion, Jumbo functions not only as entertainment but also as an effective educational medium for teaching moral values to teenagers and can contribute to character education in Indonesia.